Impact of pre-operative walking on post-operative bowel function in patients with gynecologic cancer. Issue 8 (19th July 2019) - Özdemir, İsa Aykut and Comba, Cihan and Demirayak, Gokhan and Gülseren, Varol and Erdogan, Sakir Volkan and Aslanova, Fidan and Afsar, Selim and Gungorduk, Kemal
Abstract : Background: There is a paucity of data on whether pre-operative walking and functional capacity has a direct association with post-operative gastrointestinal function in patients who have undergone surgery to treat gynecologic cancers. Objective: To explore the relationship between pre-operative walking and post-operative recovery of bowel function. Methods: This randomized trial was performed from January 1, 2018 to August 31, 2018. All patients had a diagnosis of endometrial or ovarian cancer and were scheduled for comprehensive staging. Group A served as the control group who did not walk regularly on the last night before surgery. Patients in group B walked for 30 min at an average speed of 3 km/h from 20.00 to 20.30 and 21.30. to 22.00 on the last night before surgery under the supervision of a nurse or doctor. The study was registered with clinicaltrials.gov (no: NCT03553121 ). Results: A total of 85 patients were enrolled: 43 patients were assigned to the walking group and 42 to the control group. There were no significant differences in demographics between the groups. Median age was 57.3±8.5 in the control and 59.9±9.1 in the walking group. In addition, 28 patients had endometrial cancer and 14 had ovarian cancer in the control group. 33 patients and 10 patients in the walking group had endometrial and ovarian cancer, respectively. The mean time to first flatus was shorter in the walking group than in the control group (32.5±10.4 vs 40.6±16.9 hours, respectively; p=0.010). In addition, the time to first defecation was significantly shorter in the walking group (62.8±26.7 vs 91.4±51.8 hours; p=0.002). Patients who walked before surgery were less likely to have post-operative paralytic ileus (25.0% vs 60.7%; p=0.003). Walking before the operative period and laparoscopic surgery independently protected against the development of post-operative paralytic ileus. Conclusion: Walking before surgery expedited time to bowel motility and ability to tolerate food. In addition, this method significantly decreased the risk of post-operative paralytic ileus. We consider that walking before surgery may be integrated into the pre-operative management of patients under going surgery for gynecologic cancers. Clinical trial registration: clinicaltrial.org record number: NCT03553121